2010
DOI: 10.1111/j.1462-2920.2010.02293.x
|View full text |Cite
|
Sign up to set email alerts
|

Cattle, weather and water: mapping Escherichia coli O157:H7 infections in humans in England and Scotland

Abstract: SummaryEntero-haemorrhagic Escherichia coli O157:H7 is a zoonotic pathogen, responsible for a relatively small number of food poisoning and illness outbreaks each year, when compared with other food-borne bacteria capable of causing infections in the population. Nevertheless, E. coli O157:H7 is a bacterial pathogen associated with severe human illnesses including bloody diarrhoea and haemolytic uremic syndrome occurring in both outbreak and sporadic settings. In England and Wales approximately 1% of all labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 78 publications
0
52
0
Order By: Relevance
“…3,4 E. coli O157:H7/NM is a pathogen with worldwide distribution, [5][6][7][8][9][10][11] with infections more commonly reported in northern latitudes 1,12 and in the summer. [13][14][15] E. coli O157:H7/NM may be carried by a wide range of animals, with cattle and other domestic ruminants recognized as important reservoirs. 16,17 Human infection can occur via consumption of contaminated food and beverages, recreational waters, and contact with humans or animals shedding the bacterium.…”
mentioning
confidence: 99%
“…3,4 E. coli O157:H7/NM is a pathogen with worldwide distribution, [5][6][7][8][9][10][11] with infections more commonly reported in northern latitudes 1,12 and in the summer. [13][14][15] E. coli O157:H7/NM may be carried by a wide range of animals, with cattle and other domestic ruminants recognized as important reservoirs. 16,17 Human infection can occur via consumption of contaminated food and beverages, recreational waters, and contact with humans or animals shedding the bacterium.…”
mentioning
confidence: 99%
“…Although the Shiga-toxin gene is found in all enterohemorrhagic E. coli (STEC), serotype O157:H7 alone is responsible for more than 73,000 cases of disease per year in the US, and it has been implicated in 250 deaths [1,2]; Cattle and other ruminants are natural reservoirs of E. coli O157:H7 that can introduce pathogenic E. coli into the environment through fecal shedding [3][4][5][6]. Estimates of occurrence vary, but it appears that both dairy herds and beef feedlots can have animals carrying STEC including E. coli O157:H7 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a high probability that Lake Oconee could be contaminated with STEC including E. coli O157:H7, and this could represent a serious public health risk when water from the lake is used for recreation or crop irrigation. Microbiological studies have found that waterborne transmission of STEC such as E. coli O157:H7 can occur through swimming, crop irrigation or from drinking contaminated water [7,9]. Moreover, the infectious dose of E. coli O157:H7 in humans is quite low [7].…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of drinking water from private water supplies in rural areas to VTEC contamination has been highlighted, with a private water supply being considered as one that is not provided by a water company and includes wells, boreholes, springs, streams, rivers, lakes, or ponds. Such private water supplies are common in both Ireland and Scotland, where rates of human VTEC illness are high, and in both countries private water can be considered a potentially important risk factor for VTEC human infection (87)(88)(89). A large E. coli O157 outbreak involving a private group water scheme was reported in a rural area of Ireland, involving 18 cases of infection, including 2 HUS cases (46).…”
Section: Vtec In Watermentioning
confidence: 99%